Bacteremia in female Chinese patients with systemic lupus erythematosus: a case-control study - Fangru Chen; Fei Hao; Qiquan Chen; Tian Qian; Yan Chen; Huan Wang; Zhifang Zhai (Journal of Infection in Developing Countries)
Introduction: Bacteremia is a common complication in systemic lupus erythematosus (SLE) patients, causing high morbidity and mortality. We investigated characteristics, pathogens, and sites of infection using a cohort of 64 female adults from a single university hospital in China.